Do Cognitive and Noncognitive Skills Explain the Gender Wage Gap in Middle-Income Countries? : An Analysis Using STEP Data - Tognatta, Namrata; Valerio, Alexandria; Sanchez Puerta, Maria Laura (World Bank, Washington, DC, 2016)
Gender-based wage discrimination is a highly researched area of labor economics. However, most studies on this topic have focused on schooling and paid limited attention to the mechanisms through which cognitive and noncognitive skills influence wages. This paper uses data from adults in seven low- and middle-income countries that participated in the STEP Skills Measurement Survey to conduct a comparative analysis of gender wage gaps. The paper uses schooling and skills measures, including reading proficiency and complexity of on-the-job computer tasks to proxy cognitive skills, and personality and behavioral measures to proxy for noncognitive skills in wage decompositions. The analysis finds that years of school explain most of the gender wage gap. The findings also suggest that cognitive and noncognitive skills affect men’s and women’s earnings in different ways, and that the effects of these skills vary across the wage distribution and between countries.